Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1063/1.4813505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crosslink formation on heat conduction in amorphous polymers

Abstract: We performed molecular dynamics (MD) simulations on amorphous polyethylene (PE) and polystyrene (PS) in order to elucidate the effect of crosslinks between polymer chains on heat conduction. In each polymer system, thermal conductivities were measured for a range of crosslink concentration by using nonequilibrium MD techniques. PE comprised of 50 carbon atom long chains exhibited slightly higher conductivity than that of 250 carbon atom long chains at the standard state. In both cases for PE, crosslinking sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
66
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 34 publications
10
66
0
1
Order By: Relevance
“…In amorphous polymer, previous studies have revealed that the effective crosslinking density will basically affect thermal conductivity in two ways [29,30]. On one hand, the addition of covalent crosslinking bonds will increase thermal conduction pathways between prior non-bonded chain segments, which is verified by the SEM images in Figure 2d-f. On the other hand, more crosslinking bonds will introduce more phonon scattering along the backbone chains, which reduces the phonon mean free path.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…In amorphous polymer, previous studies have revealed that the effective crosslinking density will basically affect thermal conductivity in two ways [29,30]. On one hand, the addition of covalent crosslinking bonds will increase thermal conduction pathways between prior non-bonded chain segments, which is verified by the SEM images in Figure 2d-f. On the other hand, more crosslinking bonds will introduce more phonon scattering along the backbone chains, which reduces the phonon mean free path.…”
Section: Resultssupporting
confidence: 53%
“…On one hand, the addition of covalent crosslinking bonds will increase thermal conduction pathways between prior non-bonded chain segments, which is verified by the SEM images in Figure 2d-f. On the other hand, more crosslinking bonds will introduce more phonon scattering along the backbone chains, which reduces the phonon mean free path. Particularly, when the crosslinking density is low (0~10 mol %), the two effects will cancel each other [29,30]. For large crosslinking density (10~80 mol %), the increase of thermal conduction pathway dominates, which poses a linear increase in thermal conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…This can be explained by the addition of covalent pathways which lead to higher thermal transport in the networks. Other polymers have shown similar dependence on the degree of cross-linking such as polyethylene (PE) and polystyrene (PS) shown by Kikugawa et al [12]. The cross-linking dependence observed for novolac phenolic was smaller than PE which has no aromatic carbons and larger than the thermoplastic PS.…”
Section: Mechanical Propertiesmentioning
confidence: 71%
“…Thermoset resins are well-suited for atomistic simulations which can establish the relationship between the chemical structure of the polymers and their material properties, such as mechanical [8][9][10][11] and thermal responses [12]. Recently, molecular dynamics (MD) simulations have been used to model other thermoset systems such as epoxies [13][14][15][16][17][18][19][20][21][22][23] as well as phenolic resins [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…that the H-bond-donating hydroxyl group does not attach directly to the PVPh backbone but rather via a benzene ring as a linker, similar to crosslinked polystyrene 25 .…”
mentioning
confidence: 95%